E=mc p2 s : the great ideas that shaped our world - Moore, Pete, 1962- ([New York] : Friedman/Fairfax : Distributed by Sterling Pub. Co., 2002)
A brilliant premise, but you could never understand it till now. Physics, genetics, chemistry, biology, astronomy; science is changing so rapidly that it's almost impossible for a novice to keep track of the new ideas that are shaping our present and altering our future. Here is a guide that will steer you through the modern maze of knowledge on the really big concepts that have made an impact on our world.
World around us: Nature of nature -- Structure of nature -- Earth -- Universe -- Mathematics -- Invention and innovation -- World within us: Evolution and genetics -- Human body -- Brain.
Includes index.
Keywords: Science -- Popular works; Mathematics -- Popular works